Research perspectives on functional micro- and nanoscale coatings - Zuzuarregui, Ana 1984-; Morant-Minana, Maria Carmen 1979- (Advances in chemical and materials engineering (ACME) book series, 2016)
This book highlights critical research on preparation methods, modification, organization, and utilization of functional coatings in micro, nano, and biotechnology, emphasizing emerging developments and global research perspectives